Comparison of forage yield and quality of local and commercial barley (Hordeum vulgare L.) varieties under semi-arid conditions - Tufan, Yasir; Ozkurt, Mahir; Kurt, Ayse Nida (Scientific Scholar Llc, 2026)
Livestock farming in semi-arid Eastern Anatolia is facing an increasing forage shortage due to changing climate, degraded pastures, and low-yielding genotypes of conventional forage crops. Therefore, alternative forage crops are necessary to sustain livestock production in such regions. Mud province in the Eastern Anatolia region of T & uuml;rkiye has a semi-arid climate with significant livestock production potential. Nevertheless, forage shortage is a major hurdle to sustainable livestock production. This two-year study evaluated local and commercial barley (Hordeum vulgare L.) genotypes as an alternative forage crop under natural field conditions. Fourteen genotypes were assessed based on fresh forage yield (FFY), dry matter yield (DMY), crude protein (CP), fiber fractions Acid Detergent Fiber (ADF), Neutral Detergent Fiber (NDF), digestible dry matter (DDM), and relative feed value (RFV). FFY ranged from 11330 to 20146 kg ha-1, while the DMY varied from 2945 to 5127 kg ha-1. The 'Olgun' and 'Aydanhan & imath;m' consistently produced higher yields. The CP content ranged from 15.28% to 16.34%, yielding 469 to 775 kg ha-1 of CP, and 'Olgun' and 'Line 1' proved the most efficient genotypes. The ADF (27.64-28.95%) and NDF (54.57-60.22%) values confirmed a DDM of 66.8% and the calculated RFV indicated a forage quality level exceeding the standard benchmark. Notably, the genotypes 'Bolay & imath;r' and 'Hazar' exhibited lower fiber concentrations, which corresponded to comparatively higher RFV and enhanced overall forage quality. The notable year, genotype, and year & times; genotype interactions revealed genotypic susceptibility to climatic variations. Although similar research exists, this study provides a region-specific and multi-parameter assessment of forage yield and quality under the semi-arid environmental conditions of Mud province. The results indicated that 'Olgun' and 'Aydanhan & imath;m' genotypes are best suited for high-yield, whereas 'Bolay & imath;r' and 'Hazar' are better suited for quality-focused roughage production. The results will help to improve resilient livestock feeding strategies under rainfed environments.
Keywords: Barley Forage; Crude Protein Concentration; Eastern Anatolia (T & Uuml;Rkiye); Fiber Fractions (Adf, Ndf); Genotype & Times; Environment Interaction; Rainfed Production Systems